Cryopreservation of Orchids – A Review - Kaur, Saranjeet (Recent Patents on Biotechnology, 2019)
Background: The orchids are one of the beautiful creations of nature which stand apart from any other assemblage of flowering plants. They are highly evolutionary and ecologically significant group of plants that have effectively occupied almost every habitat on the earth. Indiscriminate collections and extermination of their natural habitats have threatened many species of orchids with extinction, resulting in a severe reduction of their genetic resources in nature according to recent patents. It is necessary to adopt sound scientific protocols for the preservation of orchid species. Method: This cost-effective technique provides large storage time for the conservation of germplasm. Presently, efforts have been made to explore various cryopreservation techniques utilized so far and factors affecting the longevity of the propagules (in vivo and in vitro) while cryopreserving them. The sample to be cryopreserved is freeze-preserved in two ways, a) stepwise at two different subzero temperatures and b) in the rapid method, the samples are placed directly in the liquid nitrogen. Results: The orchid seeds and pollen are the most suitable propagules for cryopreservation of orchids due to their minute size and less space requirement. Conclusion: Among the tissues (such as seeds, pollen, protocorms etc.) seeds are the most reliable. The present article reviews the cryopreservation techniques and factors effecting the cryopreservation, for in vitro conservation of orchid gene pool.
Keywords: orchids